Context-specific Knowledge Is the "Key" to Salsa Music. Issue 1 (3rd April 2021) - Getz, Laura M.; Barton, Scott; Perry, Lynn K.
ABSTRACT: Introduction: Previous research has shown ways in which both formal training and informal exposure affect perceptual experience and the development of musical abilities. Here we asked what types of training and exposure are necessary to acquire the context-specific knowledge associated with expertise. We specifically focused on the perception of salsa music: a genre that is rich in rhythmic complexity, but has received relatively little attention in experimental settings. Methods: We examined specific groups within the exposure and training populations: those with musical training in the production of salsa rhythms (Study 1) and "native listeners" who grew up listening to salsa music without formal training (Study 2). Using two clave patterns (3–2 and 2–3 son clave) and three constructed alternatives, we asked participants to choose the correct clave pattern for a variety of music excerpts. Results: We found that informal listening exposure was not enough to detect the salsa–clave pairings. Instead, proficiency was only developed when training and exposure were both domain-specific. Discussion: Our results show the importance of deliberate training and the degree to which expertise comes to fruition through context-specific focus, thus helping to illuminate the complex relationship between the local and the universal in musical-cultural experience.